Oscillatory mechanics at 36 weeks post-menstrual age as markers of lung disease in preterm infants: a cohort study. Issue 6 (2nd June 2022) - Zannin, Emanuela; Rigotti, Camilla; Neumann, Roland P.; Dellacà, Raffaele L.; Schulzke, Sven; Ventura, Maria Luisa
Bronchopulmonary dysplasia (BPD) is the most frequent morbidity of preterm birth and is characterised by abnormal or arrested pulmonary development. Current definitions of BPD suffer from the limitation that they are based on treatment at specific time points [1, 2]. Lung mechanics may provide continuous markers of lung disease, independent from unit policies, which could be repeated over time during the evolving phase or follow-up. Respiratory system resistance and reactance assessed at 36 weeks post-menstrual age by the forced oscillation technique are sensitive functional markers of the severity of lung disease in former preterm infants https://bit.ly/3rZBq6z